Mechanical Tissue Resuscitation (MTR): A Nonpharmacological Approach to Treatment of Acute Myocardial Infarction. Issue 8 (4th June 2015) - Jordan, James E.; Pereira, Beatriz D.; Lane, Magan R.; Morykwas, Michael J.; McGee, Maria; Argenta, Louis C.
ABSTRACT Background and Aim Myocardial ischemia‐reperfusion injury is known to trigger an inflammatory response involving edema, apoptosis, and neutrophil activation/accumulation. Recently, mechanical tissue resuscitation (MTR) was described as a potent cardioprotective strategy for reduction of myocardial ischemia‐reperfusion injury. Here, we further describe the protective actions of MTR and begin to define its therapeutic window. Methods A left ventricular, free‐wall ischemic area was created in anesthetized swine for 85 minutes and then reperfused for three hours. Animals were randomized to two groups: (1) untreated controls (Control) and (2) application of MTR that was delayed 90 minutes after the initiation of reperfusion (D90). Hemodynamics and regional myocardial blood flow were assessed at multiple time points. Infarct size and neutrophil accumulation were assessed following the reperfusion period. In separate cohorts, the effect of MTR on myocardial interstitial water (MRI imaging) and blood flow was examined. Results Both groups had similar areas at risk (AAR), hemodynamics, and arterial blood gas values. MTR, even when delayed 90 minutes into reperfusion (D90, 29.2 ± 5.0% of AAR), reduced infarct size significantly compared to Controls (51.9 ± 2.7%, p = 0.006). This protection was associated with a 33% decrease in neutrophil accumulation (p = 0.047). Improvements in blood flow and interstitial water were also observed. Moreover, we demonstrated that the therapeutic window for MTR lasts for at least 90 minutes following reperfusion. Conclusions This study confirms our previous observations that MTR is an effective therapeutic approach to reducing reperfusion injury with a clinically useful treatment window. doi: 10.1111/jocs.12580 (J Card Surg 2015;30:659–667)